Competitive annealing mediated isothermal amplification of nucleic acids. Issue 3 (10th January 2018) - Mao, Rui; Qi, Lifei; Li, Jianjun; Sun, Ming; Wang, Zhuo; Du, Yuguang
Abstract : A novel nucleic acid isothermal amplification method with high specificity, efficiency and rapidity was developed. Abstract : A novel nucleic acid isothermal amplification method with high specificity, efficiency and rapidity was developed. The principle of primer design was achieved by slight modification of PCR primers. Acceleration probes were also explored. The newly developed method is of great potential for point of care diagnostics.